Manajemen Berbasis Nilai, Studi Atas Penerapan Manajemen Berbasis Nilai - Lilis Sulastri (Kontigensi : Jurnal Ilmiah Manajemen, 2014)
The study on the practice of value-based management was conducted at Binus University.This study is a single case study that uses qualitative method and snowball sampling technique.Data was collected through observation, interviews, in-depth interviews, and documentation. Researchers then conducted an analysis and interpretation of data related to values-based management practice and it’s impact on sustainable competitive advantage of Binus University. This study states us that value-based management plays an important role in management practices contained at Binus University as a public institution. Value-based management is implemented through two complementary stages: (1) value creation as the initial process of values institutionalization ​​in management practices, and (2) value management as an effort to maintain and incorporate those values ​​to a character on a personal level, and culture at the organizational level. The results further show us that value based management have a significant impact to sustainable competitive advantages of Binus University, which can be seen from the achievements of the institution, a high level of public trust, as well as the interest of the company to graduate students of Binus University.